Analysis of kinetics, mechanism, thermodynamic properties and product distribution for pyrolysis of Ni–Fe impregnated coconut husk - Kumar R.; Dubey P.; Mondal M.K. (My University, 2025)
This study explored on pyrolytic thermal degradation of coconut husk (CH), treated with Ni–Fe electroplating wastewater and Ni–Fe synthetic water, for bioenergy generation. Initially, green coconut husk absorbed solutions resembling electroplating effluent and synthetic Ni–Fe at 105 °C. Physiochemical properties of the husk and ICP-MS analysis of water were thoroughly examined before TG/DTG analysis. The impact of catalysts on pyrolysis was assessed through TG/DTG measurement, the obtained results were utilized to study the kinetics and thermodynamic parameters using the iso-conversional approaches (FWO, KAS, Starink) and Criado plots were used to discuss the reaction mechanism. Metal impregnated biomass with wastewater (MICHw) found to have high activation energy compared to that of metal impregnated with synthetic water (MICHs). For MICHw, average activation energies were calculated as 132.22, 151.37, and 149.78 kJ/molefegurefff for FWO, KAS, Starink, respectively, however, for MICHs the values were 114.79, 114.03.71, and 114.75 kJ/mol. The potential energy barrier (6–10 kJ/mol) between activation energy and reaction enthalpy showed a favourable environment for product development. Various experiments on native green coconut husk (NGCH) and impregnated coconut husk under different conditions showed a higher liquid oil yield for MICHw, attributed to the Ni–Fe catalyst at 650 °C and smaller particle sizes. This research provides key insights into enhancing bioenergy production through the pyrolytic conversion of impregnated coconut husk, highlighting the pivotal role of wastewater-derived catalysts. © 2024